Urea as an Ammonia Surrogate in the Hantzsch’s Synthesis of Polyhydroquinolines / 1,4-dihydropyridines under Green Reaction Conditions - Dhananjaya, G.; Raghunadh, Akula; Kumar, P. M.; Reddy, S. Pulla; Murthy, V. Narayana; Anna, Venkateswara Rao; Pal, Manojit (Letters in Organic Chemistry, 2021)
Synthesis of polyhydroquinolines via Hantzsch’s multicomponent reaction (MCR) involves the use of a hygroscopic and moderately toxic ammonium salt as one of the key reactants. In our effort, we have found urea as an effective ammonia surrogate when the MCR was performed in the presence of sulphonic acid-functionalized Wang resin (Wang-OSO3H) as a polymeric and recoverable acidic catalyst under green conditions. Urea is relatively less hygroscopic/toxic than the commonly used ammonium salts used in this MCR. The methodology afforded a range of polyhydroquinolines in good yields. Depending on the nature of reaction conditions employed, the MCR afforded Biginelli product or 1,4-DHPs when the use of 1,3-diketone was omitted.
Keywords: Catalyst